The Politics of The Law of Organizing the Election of Regional Heads and Deputy Heads of Regions Reviewed From Aspects of the Constitutional Court's Decision - Faradillah Faradillah (Indonesia Prime, 2020)
Political Law elections of regional heads and deputy heads of regions is the policy of the state to form and apply hukum in regulating the implementation of elections of regional heads and deputy heads of regions in order to achieve the national goals of the nation and the country whose results (output) in the form of legal products (laws, government regulations, and other regulations). The formulation of the problem is how is the decision of the Constitutional Court that shows the political development of the law in the implementation of regional elections and deputy heads of regions in the era of direct democracy? The method of approach used in this writing is normative juridical by reviewing the birth of various legal products to follow up the Decision of the Constitutional Court relating to the implementation of the Election of Regional Heads and Deputy Heads of Regions.